FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KETUBAN PECAH DINI (KPD) PADA IBU BERSALIN DI RUMAH SAKIT BAKTI TIMAH KOTA PANGKALPINANG - Siti Patimah, Siti Patimah; Elistia, Vany; Kusumajaya, Hendra; Ayudita (Biro Akademik, Penelitian dan Pengabdian kepada Masyarakat, Universitas Anak Bangsa, 2024)
PRM is one of the causes of the Maternal Mortality Rate (MMR). In Indonesia, the incidence of PRM ranges from 8-10% of all pregnancies. The PRM rate reaches 3-10% of childbirth. In general, this study aims to find out the factors related to the incidence of premature rupture of membranes in pregnant women at Bakti Timah Hospital, Pangkalpinang City in 2023. This study uses a quantitative method with a Case Control design. The instrument used was secondary data from medical records at Bakti Timah Hospital, Pangkalpinang City. The population of this study is all mothers giving birth at Bakti Timah Hospital in 2023, the number of samples of 146 people consists of 73 case groups (mothers giving birth with PRM) and 73 control groups (mothers giving birth without PRM). Sampling was done using Nonprobability sampling techniques. The statistical test used is the Chi Square test. The result showed that there was a meaningful relationship between maternal age, namely 2,859 times at risk, parity at 2,936 times at risk, and occupation at 2,898 times at risk and KPD history 5,867 times at risk of experiencing PRM in pregnant women at Bakti Timah Hospital, Pangkalpinang City in 2023. The result of the study are expected to be used as input to improve the quality of services for pregnant and maternity women so that they can reduce the incidence of PRM and at the same time reduce the maternal mortality rate. Keywords: Premature Rupture of Membranes, Pregnant Women, Maternal age, Occupation